Performance enhancement and optimization of residential air conditioning system in response to the novel FAl2O3-POE nanolubricant adoption - Nugroho, A.; Rizalman, Mamat; Xiaoxia, J.; Bo, Z.; Mohd Faizal, Jamlos; Mohd Fairusham, Ghazali (Elsevier Ltd, 2023)
This paper aims to evaluate residential air conditioning systems' performance enhancement and optimization by adopting a novel functionalized Al2O3 (FAl2O3)–Polyolester (POE) nanolubricant. Comprehensive discussions were conducted on key performance parameters, including heat absorption, compressor work, cooling capacity, coefficient of performance (COP), and power consumption. Novel FAl2O3 nanoparticles were dispersed into the POE lubricant using a two-step method. The findings reveal that FAl2O3–POE nanolubricant exhibits superior heat absorption compared to pure POE. Heat absorption decreases with an increased initial refrigerant charge, while cooling capacity performance improves with an increased initial refrigerant charge. The COP shows an increasing trend at all concentrations of FAl2O3–POE nanolubricant when operating with R32. FAl2O3–POE/R32 demonstrates an enhanced range of 3.12%–32.26% for COP. The results suggest that applying novel FAl2O3–POE nanolubricant with R32 can reduce electrical power consumption by 13.79%–19.35%. The central composite design (CCD) offers an optimal condition for FAl2O3–POE nanolubricant with a concentration of 0.11 vol%, an initial refrigerant charge of 0.442 kg, resulting in a COP of 3.982, a standard error of 0.019, and a desirability of 1.0.